A novel implementation of backpressure algorithm in wireless ad hoc network - Addagatla, Ugendhar; Janaki, V. (International Journal of Engineering and Technology, 2017)
In the wireless networks, the routing technique is the one of the highest concern and it is the important procedure in the ad hoc networks. To aid this effort, we proposed a new valuation of backpressure appliances for wireless networks. By this proposed system, we will address numerous preparation and routing difficulties and also recover the throughput and delay that are essentially produced by the packets at the node transmission. The Backpressure routing is a dense and enlarged throughput for wireless networks, but endures improved delays. In routing, the backpressure algorithm is known to afford throughput optimality with active traffic. The significant supposition in the backpressure algorithm is that all nodes are kind and detect the algorithm rules leading the information conversation and principal optimization necessities. In the proposed system, we validate that how the node is steady at the backpressure algorithm routing and also by together easing the virtual trust line and the real package queue. The backpressure algorithm not only achieves flexibility, but also stands the throughput performance under safety attacks. This scheme is mostly enhances the node performance at the time of announcement and also it recovers the node security at the time of numerous threats in the wireless requests.